Surprising Hofmeister Effects on the Bending Vibration of Water. Issue 20 (19th August 2016) - Yan, Chuanyu; Xue, Zhimin; Zhao, Wancheng; Wang, Jinfang; Mu, Tiancheng
Abstract: The Hofmeister series, which originally described the specific ion effects on the solubility of macromolecules in aqueous solutions, has been a long‐standing unsolved and exceptionally challenging mystery in chemistry. The complexity of specific ion effects has prevented a unified theory from emerging. Accumulating research has suggested that the interactions among ions, water and various solutes play roles. However, among these interactions, the binding between ions and solutes is receiving most of the attention, whereas the effects of ions on the hydrogen‐bond structure in liquid water have been deemed to be negligible. In this study, attenuated‐total‐reflectance Fourier transform infrared spectroscopy is used to study the infrared spectra of salt solutions. The results show that the red‐ and blue‐shifts of the water bending band are in excellent agreement with the characteristic Hofmeister series, which suggests that the ions' effects on water structure might be the key role in the Hofmeister phenomenon. Abstract : Bending with the wind : The blue‐/red‐shifts of water bending vibrational peak in infrared spectroscopy show that the chaotropes and kosmotropes of the Hofmeister series have opposite effects on the structure of water.